IMPLEMENTATION OF PERSUASIVE COMMUNICATION ETHICS IN ANIES BASWEDAN’S SPEECH IN THE PRAMONO-RANO CAMPAIGN - Rosa, Cut Nabila (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
This study analyzes the application of Persuasive Communication Ethics in Anies Baswedan’s speech during the Pramono-Rano campaign in South Jakarta. Using Perloff’s (2021) framework, the research evaluates five key components: symbolic advice, influence-oriented goals, non-confrontation, message clarity, and absence of coercion. Employing a qualitative approach with data triangulation, the study examines how Anies’s speech aligns with ethical persuasive communication principles. Findings reveal that Anies effectively utilized symbolic themes, emphasized unity and progress, avoided confrontation, delivered clear and motivating messages, and encouraged voluntary participation without coercion. These strategies demonstrate a commitment to ethical persuasion in a political context, fostering public trust and engagement